DEVELOPMENT OF A COMPUTER SCIENCE APPLICATION BASED ON AUGMENTED REALITY TECHNOLOGY - Baiganova А.М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The purpose of the research described in this article is to study the issues of the problems of developing applications based on augmented reality technologies in computer science education. The article discusses the methods used for application development, the process of choosing a programming environment and the stages of creation.The selected environment is Unity, Vuforia.Vuforia is a free and constantly updated library that allows you to create cross-platform applications using a special Unity game engine. The SDK supports both iOS and Android languages and allows you to create augmented reality applications in Unity that can be easily transferred to both platforms simultaneously.Applications developed using are compatible with a wide range of mobile devices, including phones and tablets running iPhone, iPad, Android and Android OS. Research methods-programming methods in an integrated environment, programming technology, methods of designing mobile applications. As a result of the research, augmented reality technologies in education were studied, programming environments for application development were analyzed, and a computer science application based on AR technology was developed.